Análise espacial das aglomerações da indústria de transformação nos segmentos moderno e tradicional no estado do Paraná - Prestes, Andréia Ferreira (2019)
The location of industries and the formation of industrial gatherings become important for the economic dynamics, whereas the agglomeration can represent the region’s well being. The installation of a company, besides to create employment and increasing consumption, can also attract new investments, forming agglomeration that leads to industrial concentration in space, thus contributing to development and wealth generation, not only for the region, but also in its around. It is important noted that the technological level of these companies can influence the results produced for the region. In this way, the identification of the reasons that induce to the locational choice of industries with different technological content and the formation of agglomerates, becomes essential for the understanding the dynamics and the promotion the regional economic development. For this reason, this research aims to analyze spatially the causes of agglomeration of the transformation industry (IT), especially between the modern and traditional segments, for the counties of the Parana State in the year 2017. In addition, it intends to verify if the agglomerations of IT follow a spatial model and if there is a relation between the concentration of the segments and the level of instruction of the counties. In order to attend these objectives, the IT sectors were divided into two segments: traditional and modern, the first there are the sectors with low technological content, low remuneration and qualification of the workforce; in the second, there are the sectors with the highest technological progress and the most qualified and best paid workers. In order to measure the industrial concentration of each segment and in each county, the Normalized Concentration Index was constructed, using the number of jobs in each segment. Later, to verify the distribution in the space and the relation between the concentration of the segments and the level of instruction, it was used the Exploratory Analysis of Spatial Data. And finally, through spatial econometrics, the causes that led to industrial concentration in the different segments were estimated. The results showed that the traditional segment operates with higher intensity in the state of Paraná than the modern segment, besides not presenting a uniform spatial pattern. Regarding education, the traditional segment obtained positive autocorrelation until high school, in turn, the modern segment needs a skilled workforce and therefore tends to attract workers with a higher level of instruction. The application of the econometric models made it possible to infer that the traditional segment has spatial impact influencing the counties and their neighborhood, diferently from the modern segment that did not reach significance. In addition, the factors influencing the locational decision are, in the great majority, different for each segment, and when the same ones presented an inverse relation, it is the case of transportation cost and income. With the divergence between the segments, it is concluded that the locational decision and the formation of agglomerates, labor-intensive or capital-intensive, have a different impact on the population, the institutions, the development of the region and the counties around.